Genome Evolution of Photosynthetic Bacteria - Beatty, J. Thomas, 1949- (Advances in botanical research, 2013)
Advances in Botanical Research publishes in-depth and up-to-date reviews on a wide range of topics in plant sciences. The series features a wide range of reviews by recognized experts on all aspects of plant genetics, biochemistry, cell biology, molecular biology, physiology and ecology. This thematic volume features reviews on genome evolution of photosynthetic bacteria. Publishes in-depth and up-to-date reviews on a wide range of topics in plant sciencesFeatures a wide range of reviews by recognized experts on all aspects of plant genetics, biochemistry,